Perlindungan Anak Dalam Penyelesaian Perkara Harta Bersama Dengan Objek Rumah Tempat Tinggal Anak (Studi Putusan Mahkamah Agung No. 61 K/AG/2025) - Muhammad Adiaat; Andhani Novita Putri (JOURNAL of LEGAL RESEARCH, 2026)
Disputes over joint property following divorce frequently generate complex issues, particularly when the disputed object constitutes the primary residence of minor children. This research examines the resolution process of joint property division cases in Religious Courts and judicial considerations in providing protection to children, specifically through analysis of Supreme Court Decision Number 61 K/AG/2025. The research employs a normative juridical approach by analyzing relevant legislation and court decisions. Findings indicate that the joint property case resolution process encompasses stages from filing suit, trial proceedings with mediation attempts, evidence presentation, through execution of judgments. In the examined case, significant differences emerged between the legalistic considerations of Religious Court and Religious High Court judges versus the Supreme Court 2019 emphasis on justice and benefit principles. This research provides important contributions to judicial practice in balancing parental rights with child protection rights in joint property cases.